(untitled) (Journal of Physical Education (Maringá), 2019)
The purpose of this study was to analyze the effects of circuit resistance training (CRT) on blood biomarkers of cardiovascular disease risk in older women. Nineteen physically independent older women (â‰¥ 60 years) were randomly assigned to one of the two groups: control (CG, n = 9) and CRT (n = 10). The CRT performed a resistance exercise program for 12 weeks, with 10 exercises: unipedal balance, squat, bench press, seated row, triceps push-down, preacher curl, shoulder adduction, throw medicine ball into the floor, stationary run, and abdominal isometric contraction, with three sets per exercise. Anthropometry, total cholesterol, triglycerides, low density lipoprotein cholesterol (LDL-c), high density lipoprotein cholesterol (HDL-c), very low-density lipoprotein cholesterol (VLDL-c), glucose were measured. Main effect of time (p < 0.05) was observed for total cholesterol (-9.9%), LDL-c (-16.1%), VLDL-c (-15.9%) and HDL-c (+10.2%) in the CRT. The composite Z-score was reduced significantly for the CRT group but not for CG. The 12 weeks of CRT were effective for reducing total cholesterol, LDL-c, VLDL-c, triglycerides and increase HDL-c. In addition, the decrease in composite Z-score suggests that CRT can reduce cardiovascular disease risk in older women.